Inovasi Pemerintahan Kabupaten Banyuwangi Melalui City Branding â€œThe Sunrise Of Javaâ€ Sebagai Strategi Pemasaran Pariwisata. - Fikri, Haidar (Universitas Muhammadiyah Ponorogo, 2017)
Branding becomes important in introducing something that you want to offer to masayarakat.Tentu, the government should look at it all because if you want to introduce to the local travel nationally and internationally should give a brand easily recognized and remembered as well as a differentiator with lain.Cirikhas area of a branding is what will be the strategy for the government to offer travel how an area will be known. As well as the use of branding Banyuwangi